1990
DOI: 10.1002/food.19900340415
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in cereal grain Part 14. Histochemical examination of fusarium‐damaged wheat kernels

Abstract: Wheat kernels with visible Fusarium-damage, naturally infected, have been examined with histochemical techniques to observe mycelium growth inside kernels and change in kernels cells. Kernels infected with F. culmorum were found to be damaged more extensively, comparatively to those infected with F. graminearum, F. avenaceum and F. nivale/(Microdochium nivale). Growth of Fusarium mycelium was most abundant between pericarp and aleurone layer and alongside of scutellum. Mycelium colonized also endosperm and emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…Many more destroyed and broken granules were observed in the seriously infected samples in comparison to the lightly infected ones, indicating a substantial structural alteration in the endosperm. Nightingale et al (5) also found that in severely infected areas within the kernel, the starch granules had begun to show symptoms of amylolytic degrada- tion, a finding that was in agreement with the conclusions of other authors (4,22). The results in the present study appeared to substantiate this too, as it was suggested that the starch granule destruction reflected the fungal infection.…”
Section: Resultssupporting
confidence: 94%
“…Many more destroyed and broken granules were observed in the seriously infected samples in comparison to the lightly infected ones, indicating a substantial structural alteration in the endosperm. Nightingale et al (5) also found that in severely infected areas within the kernel, the starch granules had begun to show symptoms of amylolytic degrada- tion, a finding that was in agreement with the conclusions of other authors (4,22). The results in the present study appeared to substantiate this too, as it was suggested that the starch granule destruction reflected the fungal infection.…”
Section: Resultssupporting
confidence: 94%
“…Microscopic examination of the tombstones indicates that damage is so severe that definitive tissue structures are lacking (Chelkowski et al, 1990). Microscopic examination of the tombstones indicates that damage is so severe that definitive tissue structures are lacking (Chelkowski et al, 1990).…”
Section: Tissue-specific Activation/suppressionmentioning
confidence: 99%
“…On a weight basis, tombstones contain more DON than kernels that are able to fully mature (Reid et al, 1996;Sinha & Savard, 1997). Analysis of the denser, less diseased kernels indicates that DON contamination is distributed in all kernel fractions, that is, endosperm, germ, and pericarp (Hart & Braselton, 1983;Chelkowski et al, 1990;Schaafsma et al, 2004). Analysis of the denser, less diseased kernels indicates that DON contamination is distributed in all kernel fractions, that is, endosperm, germ, and pericarp (Hart & Braselton, 1983;Chelkowski et al, 1990;Schaafsma et al, 2004).…”
Section: Tissue-specific Activation/suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces. (Chelkowski et al 1990). Fusarium mycelium growth was found to be highest between the pericarp and aleurone layers.…”
mentioning
confidence: 99%